Enriching the multi-level perspective by better understanding agency and challenges associated with interactions across system boundaries. The case of care farming in the Netherlands: Multifunctional agriculture meets health care. (January 2018) - Hassink, Jan; Grin, John; Hulsink, Willem
Abstract: The multi-level perspective (MLP) is broadly and successfully used as a framework for understanding transitions. However several aspects need more attention like agency, interactions across system boundaries and multi-regime interactions. We used our detailed and contextualized knowledge and analysis of the developing care farming sector in the Netherlands to increase our understanding of the role of agency and challenges and successful strategies of actors associated with interactions across system boundaries. We used entrepreneurship, institutional entrepreneurship and social movement theory to better understand agency in MLP. Connecting separated sectors, overcoming lack of legitimacy, lack of embeddedness and dealing with different logics were challenges associated with the care farm innovation that transcends system boundaries. Actors with a dual identity and combining entrepreneurial and institutional behavior and actors connecting with embedded actors with corresponding logics were important in overcoming these challenges. Highlights: We present detailed information of the development of the care farming sector in the Netherlands. We increased understanding of agency and enriched MLP using (institutional) entrepreneurship and social movement theory. We increased understanding how actors deal with challenges associated with interactions across system boundaries.